(untitled) (Orinoquia, 2017)
This article outlines a design for a low-cost micro-viscometer, using a quartz crystal resonator (QCR) and an Arduino DUE programmable microcontroller board. The article explains the steps involved in designing the sensor and also how it was evaluated regarding two liquids having different characteristics: dilute aqueous glycerol (Newtonian behaviour) and dilutions of egg-white extracted from fresh eggs in water (non-Newtonian behaviour). This study was related to interest in developing new tools for diagnosing cardiovascular and arthritic diseases.